The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3310/phr07110
|View full text |Cite
|
Sign up to set email alerts
|

A workplace-based intervention to increase levels of daily physical activity: the Travel to Work cluster RCT

Abstract: Background There may be opportunities for working adults to accumulate recommended physical activity levels (≥ 150 minutes of moderate-intensity physical activity in bouts of ≥ 10 minutes throughout the week) during the commute to work. Systematic reviews of interventions to increase active transport indicate that studies are predominantly of poor quality, rely on self-report and lack robust statistical analyses. Objectives T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Consequently, choosing one active mode of commuting to and from university can make a large difference in the annual energy expenditure, as concluded in [ 26 ]. The current data concur with a study carried out in an English adult population that showed that active and public mode of commuting to work were important contributors to PA levels [ 54 ]. In addition, a study in university students from The United States showed that an increase of the energy expenditure per day, week, and year may result in gradual and sustained long-term improvements in cardiometabolic health [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, choosing one active mode of commuting to and from university can make a large difference in the annual energy expenditure, as concluded in [ 26 ]. The current data concur with a study carried out in an English adult population that showed that active and public mode of commuting to work were important contributors to PA levels [ 54 ]. In addition, a study in university students from The United States showed that an increase of the energy expenditure per day, week, and year may result in gradual and sustained long-term improvements in cardiometabolic health [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is suggested that appropriate interventions are implemented to enhance MVPA within the university workplace, to ensure employees are provided with opportunities to be active during working hours. For example, some of the commonly applied and existing interventions focus on walking using step counters (Chomistek et al, 2017), encouraging stair use (Engelen, Gale, Chau, & Bauman, 2018), and active travel to work (e.g., cycle to work scheme or walk to work) (Audrey et al, 2019;Bauman, Crane, Drayton, & Titze, 2017) to improve employees PA engagement in the workplace (Ryde & Brown, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To Consistent with prior studies (Audrey et al, 2019;Carriedo et al, 2020;Foster et al, 2011;Shaw et al, 2007;Wilbur et al, 2006Wilbur et al, , 2013, our study provided for multiple recruitment strategies, inperson and electronic, that were developed with thorough planning before the onset of the COVID-19 pandemic. Not surprisingly, the percentage of potential participants who heard about the study inperson from program staff went down while institutional emails went up post-COVID-19 onset.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to facilitate recruitment of potential participants with added flexibility and convenience (Carroll et al, 2011 ; Foster et al, 2011 ; Wilbur et al, 2006 ) we planned to incorporate electronic recruitment strategies. We used emails associated with women's employment at the institution, which has been found to be an effective recruitment strategy at workplace settings (Audrey et al, 2019 ). We collaborated with key stakeholders (e.g., human resources, clinicians, and staff) to receive input regarding wording for study description, color, logos, and photographs used for recruitment (Foster et al, 2011 ; Wilbur et al, 2006 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%